Age-related effects and gender differences in Japanese healthy controls for [123I] FP-CIT SPECT - Yamamoto, Hideo; Arimura, Shinichi; Nakanishi, Atsushi; Shimo, Yasushi; Motoi, Yumiko; Ishiguro, Koichi; Murakami, Koji; Hattori, Nobutaka; Aoki, Shigeki (Annals of nuclear medicine, 2017)
Objective Dopamine transporter (DAT) imaging with [ 123 I]FP-CIT (DaTSCAN) is a widely used diagnostic tool for Parkinsonism and dementia. Since it was approved by the Japanese Ministry of Health, Labor, and Welfare in 2013, there have been no articles focusing on a Japanese normal population. The aim of this study was to examine the effect of aging and gender on DAT availability in Japanese people. Methods SPECT imaging of 30 healthy Japanese controls (17 males, 13 females; range 50–86 years, mean 70 years) was performed. SPECT images were reconstructed using a three-dimensional order subset expectation maximization (OSEM) algorithm with correction of the point spread function and scatter correction, without attenuation correction. The specific binding ratio (SBR) was calculated by DATview software. Statistical analyses were performed using linear regression analysis, analysis of variance, and multiple comparison analysis. Results A strong correlation between the SBR and age was observed. The correlation coefficient in males and females were −0.566 and −0.502, respectively. The analysis of variance revealed that aging led to a decline of the SBR, and a significant difference ( p = 0.005) was observed among generations. Gender also affected the SBR, and there was a significant difference between males and females ( p = 0.036). The SBR in females was higher than in males. Consequently, the multiple comparison revealed a significant difference between 50s and 70s ( p = 0.015) and 50s and 80s ( p = 0.006). Conclusions This is the first [ 123 I]FP-CIT SPECT study on subjects with normal dopamine function in Asian countries. This study provides a database of [ 123 I]FP-CIT SPECT in Japanese healthy controls. Higher DAT availability was found in women than in men. An average age-related decline in DAT availability of 8.9% was found in both genders. The data collected in this study would be helpful for Japanese physicians to make a differential diagnosis in Parkinsonian syndrome. The registration identification number for this study is UMIN000018045.